The Influence of Low and Moderate Carotid Stenosis on Neurophysiologic Status of Patients Undergoing on-pump Coronary Artery Bypass Grafting - Trubnikova, Olga; Tarasova, Irina; Barbarash, Olga (Frontiers in Neurology, 2012)
Background: Significant (>70%) extracranial stenosis of the internal carotid artery (ICA) is a known risk factor for brain damage in patients with coronary heart disease (CHD) undergoing coronary artery bypass grafting (CABG). There is no clear evidence of the low and moderate ICA stenoses influence on the neurophysiologic status of patients after CABG. This work was aimed at studying the influence ICA stenoses (<50%) on the dynamics of neurophysiologic status in patients undergone CABG. Methods: We examined neurophysiologic functions and EEG in CHD patients (N=45) aged from 45 to 70 years. All patients were divided into two groups: with ICA stenosis (n=20) and without one (n= 25). Results: It was established that the group ICA stenosis had a negative dynamics of neurophysiologic status 6 months follow-up after CABG compared with patients without stenosis. Conclusions: Our results suggest that the presence of low and moderate ICA stenosis is one of the factors affecting the neurophysiologic status of CHD patients. It has been assumed that the patients with ≤50% ICA stenoses constitute a high-risk group for cerebral complications after on-pump CABG.